Error Analysis on the Use of Affixation in Indonesian Paper Written By Thai Student - Kalee, Susrina; Rasyid, Yumna; Muliastuti, Liliana (Bina Nusantara University, 2018)
This research aimed to describe the form of errors in using affixation in Indonesian Language paper written by Thai students. The data were words and sentences that contained errors. The research was qualitative research using content analysis method. This research used interactive model data analysis through three steps. Those were data reduction, presentation of data, as well as conclusion and verification. The results show that there are some errors; 72 errors in using affixation: 21 or 29% errors in prefix, 9 or 13% errors in suffix, 9 or 13% errors in confix, and 33 or 46% errors klofiks (combination of affixes). The error is caused by two factors; 7% of interlingual errors and intralingual factor including 7% of overgeneralization and 86% of ignorance of rule restriction. However, the results also show that Thai students have not mastered or understood the structure of Indonesian language. The results can be used to develop the techniques of teaching Indonesian structure, especially the use of affixation. Therefore, the Thai students can improve the ability to use Indonesian language by channeling it in academic writing.